Comparative analysis of post quantum standards for electronic signature based on multivariate quadratic transformations - Gorbenko, I.D.; Kudryashov, I.S.; Onoprienko, V.V. (Radiotekhnika, 2018)
The results of the analysis and comparison of electronic signature mechanisms using multidimensional transformations in quadratic finite fields are presented. The key and electronic signature lengths, as well as the computational efficiency of the signature and signature verification are used as the main criteria. Comparison made by electronic signatures LUOV, Gui, Rainbow, MQDSS, TPSig, DualModeMS, HiMQ-3 and GeMSS. These candidates are selected by unconditional private and integral unconditional criterion for cryptographic resistance to attack based on adaptive selection of messages.